Study on Optimization Potential of Fuel Economy based on CVT - Kening Zhai; Jianjun Yang; Jidong Gao; Shuangxi Liu; Yazhuo Niu; Xianfeng Zhang (Jixie chuandong)
In order to obtain the potential of the speed ratio parameter optimization of a CVT vehicle on the direct improvement of fuel economy， the first step is to obtain the distribution characteristic of engine operating condition from test data in the NEDC cycle， most of the operating conditions are located in the urban cycle are below the optimal operation curve（OOC）. Then，the area that can be optimized is evaluated according to the speed ratio control method， there is 7% of the engine operating condition in the urban cycle can be optimized，in some working conditions in the suburban cycle（when the vehicle speed is up to 70 km/h and 100 km/h）， it cannot be optimized and adjusted due to the speed ratio limited value of the CVT. According to the simulation results， only the speed ratio parameters of CVT transmission are adjusted， including adjusting some operation conditions to the optimal fuel economy curve， or optimizing in all area， or enlarging the speed ratio range of CVT transmission， and the direct contribution of the maximum fuel saving potential reaches 3.12%.